Sevoflurane preconditioning promotes mesenchymal stem cells to relieve myocardial ischemia/reperfusion injury via TRPC6-induced angiogenesis - Jinting Yang (BMC, 2021)
Abstract Background Ischemic heart diseases is one of the leading causes of death worldwide. Although revascularization timely is an effective therapeutic intervention to salvage the ischemic myocardium, reperfusion itself causes additional myocardial injury called ischemia/reperfusion (I/R) injury. Bone marrow-derived mesenchymal stem cells (MSCs) is one of the promising cells to alleviate ischemic myocardial injury. However, this cell therapy is limited by poor MSCs survival after transplantation. Here, we investigated whether sevoflurane preconditioning could promote MSCs to attenuate myocardial I/R injury via transient receptor potential canonical channel 6 (TRPC6)-induced angiogenesis. Methods The anti-apoptotic effect of sevoflurane preconditioning on MSCs was determined by Annexin V-FITC/propidium iodide staining. TRPC6, hypoxia-inducible factor-1α (HIF-1α), Chemokine receptor 4 (CXCR4) and vascular endothelial growth factor (VEGF) protein expressions and VEGF release from MSCs were determined after hypoxia and reoxygenation (H/R). Small interfering RNA (siRNA) was used to knock down TRPC6 gene expression in MSCs. The angiogenesis of human umbilical vein endothelial cells (HUVECs) co-cultured with MSCs was determined by Matrigel tube formation. Myocardial I/R mouse model was induced by occluding left anterior descending coronary artery for 30 min and then reperfusion. MSCs or sevoflurane preconditioned MSCs were injected around the ligature border zone 5 min before reperfusion. Left ventricle systolic function, infarction size, serum LDH, cTnI and inflammatory cytokines were determined after reperfusion. Results Sevoflurane preconditioning up-regulated TRPC6, HIF-1α, CXCR4 and VEGF expressions in MSCs and VEGF release from MSCs under H/R, which were reversed by knockdown of TRPC6 gene using siRNA in MSCs. Furthermore, sevoflurane preconditioning promoted the angiogenic and anti-inflammatory effect of HUVECs co-cultured with MSCs. Sevoflurane preconditioned MSCs improved left ventricle systolic function and alleviated myocardial infarction and inflammation in mice subjected to I/R insult. Conclusion The current findings reveal that sevoflurane preconditioned MSCs boost angiogenesis in HUVECs subjected to H/R insult and attenuate myocardial I/R injury, which may be mediated by TRPC6 up-regulated HIF-1α, CXCR4 and VEGF.